A study on knowledge, attitude and confidence level on pre-hospital airway management among pre-hospital care providers in Perak - Halim, Khairul Effendy Abdul (2023)
Pre-Hospital Airway Management (PHAM) is an important aspect of patient care outside the hospital setting. Pre-Hospital Care (PHC) Providers should master PHAM skills to treat patients safely. The objective of the study is to determine the level of knowledge, attitude, and confidence about PHAM among PHC Provider in the PHC Unit and to identify the factors that affect the level of knowledge, attitude, and self-confidence about PHAM. This cross-sectional study was conducted in 14 hospitals under the Malaysian Ministry of Health (MOH) in Perak using a validated digital questionnaire consists of demographics profile, knowledge, attitudes, and self-confidence involving 118 respondents. From the 3 domain scores analysed, the Knowledge domain; 35.6% (n = 42) were good. The other two which are Attitude domains; 89.8% (n = 106) and Confidence domain; 31.4% (n = 37) both were good. The study also found that there are factors that influence the domain of knowledge, which is work experience (95% CI (1.31, 9.10), p = 0.012); attitude domain factor is attending PHAM courses (95% CI (1.75, 44.84), p = 0.008); while confidence domain factor is getting enough training (95% CI (1.21, 7.06), p = 0.018). The results from this study found that only the attitude domain was good. Researchers suggest Continuous Medical Education (CME) and frequent involvement in Simulation Training related to PHAM to increase knowledge, attitude, and self-confidence.